Konsep Dasar Pendidikan Anak Berkebutuhan Khusus - Avica Feby rahmawati; nurmei yati; maya widianti (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2023)
This article reviews the Basic Concepts of Education for Children with Special Needs. Children with special needs are children who experience delays in more than two aspects of developmental disorders or children who experience deviations consisting of blind, deaf, quadriplegic, mental retardation, autism, and earning disability. The purpose of writing this article is to find out the meaning of the concept of Education for Children with Special Needs and its characteristics. This writing uses the riescet library method. Children with special needs require special educational services to help reduce their limitations in life in society and increase their potential optimally.